Still on physicians’ attitude to medical marijuana - Abayomi, Olukayode; Babalola, Emmanuel (International Journal of Basic & Clinical Pharmacology, 2017)
Desai and Patel highlighted in a recent review that “there are several issues related to medical marijuana, which concern public health such as its medical use, harmful effects, laws and physicians role.” Certainly, physician’s perspectives and position on the relative harm and benefits of marijuana contribute to the growing controversy over its legalization in western countries. Interestingly, the seeming resistance of physicians in western countries to marijuana prescription appears to mirror the position of psychiatrists in developing countries. For instance, in a recent survey of psychiatrists in Nigeria, up to 55% of psychiatrists were against the medical use of marijuana.